2023
DOI: 10.1371/journal.pone.0281166
|View full text |Cite
|
Sign up to set email alerts
|

Survival in a consecutive series of 467 glioblastoma patients: Association with prognostic factors and treatment at recurrence at two independent institutions

Abstract: Therapy of recurrent glioblastoma (GBM) is challenging due to lack of standard treatment. We investigated physicians’ treatment choice at recurrence and prognostic and predictive factors for survival in GBM patients from Norway’s two largest regional hospitals. Clinicopathological data from n = 467 patients treated at Haukeland and Oslo university hospitals from January 2015 to December 2017 was collected. Data included tumour location, promoter methylation of O6 methylguanine-DNA methyltransferase (MGMT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…2,3 A latest clinical study analyzed the prognosis of 467 recurrent GBM patients from two institutions and revealed that tumor location is an independent predictive factor. 4 Second, we agree that there are numerous variables interacting with each other and all these variables finally lead to a health event in a complicated way. For example, GBM patients are generally older than low-grade glioma (LGG) patients and meanwhile age is also associated with tumor-related molecular alterations like isocitrate dehydrogenase 1 (IDH1) mutation.…”
mentioning
confidence: 78%
“…2,3 A latest clinical study analyzed the prognosis of 467 recurrent GBM patients from two institutions and revealed that tumor location is an independent predictive factor. 4 Second, we agree that there are numerous variables interacting with each other and all these variables finally lead to a health event in a complicated way. For example, GBM patients are generally older than low-grade glioma (LGG) patients and meanwhile age is also associated with tumor-related molecular alterations like isocitrate dehydrogenase 1 (IDH1) mutation.…”
mentioning
confidence: 78%
“…In this study, we further discovered that the underlying mechanisms contributing to the clinical functional impairments caused by GBM and astrocytoma differ from each other. Previously, certain traditional anatomical structures such as the brainstem, corpus callosum, and thalamus have been considered as prognostic factors for poor outcomes ( 50 ). However, in this study, we went beyond anatomical boundaries and employed the VLSM method to identify ROIs that can also serve as prognostic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma type and entity (the term used in the WHO 2016 classification now changed to “type”) are associated with patient survival ( Supplementary Table S1 in the Electronic Supplementary Material [ESM]) ( 5 , 10 27 ). Survival is poorest in patients with glioblastoma, where median overall survival (OS) was between 9 ( 11 ) and 26 ( 14 ) months.…”
Section: Disease Classification Grading and Associated Survivalmentioning
confidence: 99%
“…In glioblastoma, progression predicts shorter OS as shown in recent analyses from the ETERNITY, where the median OS in patients surviving ≥5 years from glioblastoma diagnosis was 9.9 years overall but was not reached in patients without recurrence relative to 8.9 years in patients with ≥1 recurrence ( 16 ). Unsurprisingly, survival in glioblastoma is associated with treatment, including surgery and chemotherapy; in Norway, median OS was reported as 6.8 months in those receiving only biopsy and 17.2 months in those with gross total resection ( 10 ). Similar data were available for the UK, where biopsy only was associated with a median OS of 8.0 months relative to 14.9 months in those with debulking surgery ( 11 ), and for Denmark, where biopsy only was associated with a median OS of 4.7 months, compared with 15.6 months in those with gross total resection ( 28 ).…”
Section: Disease Classification Grading and Associated Survivalmentioning
confidence: 99%